THE USE OF VIDEO MATERIALS TO IMPROVE STUDENTS’ DESCRIPTIVE WRITING - Nurhidayah, Rafika; Sudarsono, Sudarsono; Supardi, Iwan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was designed to improve students’ descriptive writing through the use of video materials to the Class F students of Year - 7 in SMP N 1 Sungai Raya Academic Year 2017 / 2018 which consisted of 36 students. The research problem asked about the students’ improvement in descriptive writing in terms of organization, grammar, vocabulary and mechanic. This research applied Classroom Action Research (CAR) consisted of three cycles. Each cycle was conducted in three meetings consisted of planning, acting, observing, and reflecting. The tools to collect data were observation checklists, field notes, photographs, and written test. The findings showed that there was an improvement in quantitative analysis from cycle to cycle from 51,5 in the first cycle, 64,4 in the second cylce, and 79 in the third cycle. Meanwhile the improvement of the teaching learning behaviour in qualitative analysis was notified from the classroom observation and field notes which were discussed with collaborator. The cycle stopped in the third cycle because it has reached the criteria of classroom action research success. Through the use of video materials, the students know how to write a descriptive text appropriately. In conclusion, the research showed that the use of video materials improved the students’ descriptive writing.  Keywords: Video Materials, Writing, Descriptive Text, Classroom Action Research